Macronutrient intake and malabsorption in HIV infection: a comparison with other malabsorptive states. Issue 6 (1st December 1997) - Carbonnel, F; Beaugerie, L; Rached, A Abou; D'Almagne, H; Rozenbaum, W; Le Quintrec, Y; Gendre, J P; Cosnes, J
Abstract : Background —Wasting is a major complication of HIV infection. The role of malabsorption in wasting is controversial. Aims —To assess oral intake and malabsorption in a cohort of weight losing HIV infected patients, with or without chronic diarrhoea. Methods —A prospective study using a predefined protocol for HIV infected patients was performed in a gastroenterology and nutrition unit in a university hospital. A retrospective comparison was made with HIV negative patients with malabsorption due either to small bowel disease or resection. Body weight and height, serum albumin, oral intake of macronutrients, faecal weight, and faecal fat were measured. Results —Seventy nine weight losing HIV infected patients were studied. Among the 66 patients with more than 5% lipid malabsorption, wasting was significantly greater in patients with cryptosporidiosis (n=22) than in patients with microsporidiosis (n=18) who exhibited significantly more wasting than patients with no identified enteropathogen (n=26) (body mass index 16.8 (14.0–20.7), 18.9 (16.5–21.3), 19.7 (15.9–23), respectively). When controlling for the level of lipid malabsorption, HIV infected patients had a significantly lower energy intake than HIV negative patients with chronic malabsorption. In HIV infected patients, but not in other categories of malabsorbers, body mass index correlated significantly with energy intake ( r =0.33, 95% confidence intervals 0.12 to 0.51). Conclusion— In weight losing HIV infected patients, reduced energy intake is superimposed on malabsorption and significantly contributes to wasting.